Antimicrobial photodynamic therapy reduces gene expression of Candida albicans in biofilms - Jordão, Cláudia Carolina [UNESP]; Viana de Sousa, Tábata [UNESP]; Inêz Klein, Marlise [UNESP]; Mendonça Dias, Luana [UNESP]; Pavarina, Ana Cláudia [UNESP]; Carmello, Juliana Cabrini [UNESP] (Elsevier, 2020)
The present study evaluated whether the oxidative stress caused by antimicrobial photodynamic therapy (aPDT) affects the expression of C. albicans genes related to adhesion and biofilm formation (ALS1 and HPW1) and oxidative stress response (CAP1, CAT1, and SOD1). The aPDT was mediated by two photosensitizing agents (PSs) Photodithazine® (PDZ at 100 and 200 mg/L) or Curcumin (CUR at 40 and 80 μM) and LED (37.5 J/cm2 or 50 J/cm2). The quantification of the expression was performed by Reverse Transcription-Quantitative Polymerase Chain Reaction (RT-qPCR) using specific primers for the target genes. The data were analyzed by Analysis of Variance (α = 0.05), followed by Tukey's post-test. It was observed reduction in the expression of ALS1, HWP1, CAP1, CAT1, and SOD1 when aPDT was performed using 200 mg/L PDZ and 80 μM CUR associated to LED (37.7 and 50 J/cm2, respectively) and using 100 mg/L PDZ and 40 μM CUR with LED of 50 J/cm2 (versus control). Also, the expression of CAP1 and SOD1 genes was reduced after aPDT using 100 mg/L PDZ and LED of 37.5 J/cm2. There was a significant reduction in the expression of genes HWP1, CAP1, and SOD1 after aPDT using 40 μM CUR and 37.5 J/cm2 (versus the control group). The application of LED only at 37.5 and 50 J/cm2 promoted down-regulation of ALS1, CAP1, CAT1, and SOD1 genes (versus the control group). Therefore, aPDT mediated by LED -associated PSs PDZ and CUR promoted a reduction in the expression of the five C. albicans genes evaluated.
Keywords: Antimicrobial photodynamic therapy; Candida albicans; Virulence factors